Improving Student Learning Outcomes and Interaction in Learning Chemical Compound Nomenclature through the Application of the Domino Card Method - Zubair, Sakinah Zubair,; Alim, Zainal Alim,; Munawwarah, Munawwarah (Edukimia, 2025)
. Interactive and collaborative learning has an important role to play in improving students' academic outcomes and social skills. This study aims to explore the application of the domino card method in improving student interaction and learning outcomes in learning chemical compound nomenclature. The method used is classroom action research, which is carried out in two ways, where each cycle involves planning, implementation, observation and reflection.. The results of the study showed a significant increase in all types of student interactions, with an average of 36.46% in Cycle I to 73.27% in Cycle II. In addition, student learning completion also increased from 33.33% in Cycle I to 91.67% in Cycle II. These findings confirm that the implementation of the domino card method is not only effective in improving students' understanding of the material but also encourages active involvement and cooperation among them.. Based on the research results, it is recommended that this method be applied more widely in other learning contexts to improve the quality of education and social development of students